2020
DOI: 10.1002/mmce.22163
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturization of monopole antenna using high refractive index metamaterial loading

Abstract: In this article, miniaturization of the wire monopole antenna with the help of high refractive index (HRI) metamaterial is presented. For the first time, HRI medium is realized by using the array of single ring split ring resonator. By surrounding the wire monopole with the array of SR‐SRRs, the effective wavelength is squeezed in the vicinity of the near field dominance. By the loading of the monopole with such an HRI medium, the size of the antenna is reduced from 29.5 to 16 mm, without any deformation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…After introduction of single dielectric disc in monopole, the reactance presents at 1.49 GHz of reference monopole antenna has been cancelled out by the inductive reactance of circular dielectric disc. This results in reduction of resonant frequency of 25.12% (simulation value) unlike in [27] where miniaturization is achieve using very high refractive index meta-material. It can be noted that the proposed antenna has match the required impedance characteristic without having any matching network.…”
Section: Results and Descriptionmentioning
confidence: 99%
“…After introduction of single dielectric disc in monopole, the reactance presents at 1.49 GHz of reference monopole antenna has been cancelled out by the inductive reactance of circular dielectric disc. This results in reduction of resonant frequency of 25.12% (simulation value) unlike in [27] where miniaturization is achieve using very high refractive index meta-material. It can be noted that the proposed antenna has match the required impedance characteristic without having any matching network.…”
Section: Results and Descriptionmentioning
confidence: 99%
“…The ZOR is formed either by using ENG TL/mu negative TL or composite right/left-handed (medium) TL [81]. In [74] a wire monopole antenna is miniaturized from 29.5mm to 16 mm using an array of a single ring SRR as MTM loading. This single ring SRR arrangement increases the reactance (inductive) and permeability of the effective medium and helps to form a high refractive index medium.…”
Section: A Mtm Loadingmentioning
confidence: 99%
“…Further, it has helped to improve the impedance match performance of the proposed antenna 22 . An array of four SR‐SRR is loaded in the monopole to obtain effective miniaturization; though this technique achieves better size reduction, its design and implementation process is complex 23 …”
Section: Introductionmentioning
confidence: 99%
“…However, it does cover only single frequency band. From the above literature survey, it is observed that most of the existing antenna designs have the following issues: large size, narrow bandwidth, gain, ka, and less coverage of applications 22–42 . To address the above issues, a compact antenna design with a rectangular‐shaped split‐ring resonator (RSRR) structure is discussed.…”
Section: Introductionmentioning
confidence: 99%